Analisis Kontrak Perbankan dalam Perspektif Hukum Perdata (Studi Kasus Penerapan Hak dan Kewajiban Debitur dalam Kontrak Perbankan di Bank Panin) - Nurdiansyah, Nurdiansyah; Jadidah, Fikrotul; Mukti, Robby Teja (Postulat, 2024)
In the perspective of civil law, this contract plays an important role as it contains the elements of an agreement regulated by the Indonesian Civil Code (KUHPerdata). An analysis of banking contracts is necessary to ensure compliance with applicable laws, avoid potential disputes, and protect the rights of debtors. The rights and obligations of customers in banking contracts may vary depending on the type of product or service agreed upon. The research problem formulated in this study is how the principles of civil law regulate banking contracts and how the rights and obligations of debtors are applied in banking contracts at PANIN BANK. The research method used is normative with a regulatory approach. The results of the study show that in banking law, several principles are recognized, namely the principle of trust, the principle of prudence, the principle of confidentiality, and the principle of knowing your customer. The principle of trust is regulated in Article 29 paragraph (4) of Law No. 10 of 1998 concerning Amendments to Law No. 7 of 1992 on Banking, which states that for the benefit of debtors, banks are obliged to provide information regarding potential risks of loss related to customer transactions conducted through the bank. To gain confidence in its debtors, PANIN BANK conducts a financing assessment. The criteria for financing assessment at PANIN BANK are carried out by analyzing the 5C principles (Collateral, Character, Capital, Capacity, Condition).